NAGJUA– INNOVATIVE LANDSCAPE, AFFORDABLE LUXURY A Real -Life Case Study on Real Estate Giant- Nagjua Developers - Shubham Soni; Aditya Padhyar; Dr. Rajesh Kumar Pandey (International Journal of Engineering and Management Research, 2024)
In India, the real estate sector ranks as the second-highest employment generator, following the agriculture sector. The Indian real estate market is expected to grow to Rs. 65,000 crore (US 9.30 billion) by 2040, with a projected market size of US 1 trillion by 2030. The real estate sector comprises four sub-sectors: housing, retail, hospitality, and commercial, and is globally recognized as a key economic driver. Government initiatives, such as the Smart City Project, aim to encourage development in the real estate sector, offering opportunities for companies. This Case Study talks about the Real Estate Industry with special reference to NAGJUA developers at Silvassa. The real estate sector in the Silvassa and Vapi region has experienced significant growth driven by industrial expansion and proactive government initiatives. Nagjua, a key player in the local real estate market, is renowned for its luxurious residential properties and commitment to ecologically sustainable projects. The Nagjua Group, established in 2005, showcasing a journey characterized by strategic decision-making, visionary leadership, and a commitment to creativity and innovation. This case highlights the dilemma faced by the company and potential solutions to the dilemma.